Impact of climatic conditions projected at the World Cup in Qatar 2022 on repeated maximal efforts in soccer players - Wiktor Chodor; Paweł Chmura; Jan Chmura; Marcin Andrzejewski; Ewa Jówko; Tomasz Buraczewski; Adrian Drożdżowski; Andrzej Rokita; Marek Konefał (PeerJ, 2021)
This study aimed to investigate the relationship between the climatic conditions predicted for the 2022 FIFA World Cup in Qatar and the capacity for repeated maximum effort (RSA), of soccer players. Twenty-four semi-professional soccer players participated in the study. The exercise test consisted of ten 6-second maximal efforts on a cycloergometer. A 90-second passive rest interval was used. Mechanical parameters were recorded in each repetition, and biochemical parameters at rest and even repetitions. The test was performed in a Weiss Technik WK-26 climate chamber under two different conditions: (1) thermoneutral (TNC - 20.5 °C; 58.7% humidity); (2) predicted for the 2022 World Cup in Qatar (QSC - 28.5 ± 1.92 °C; 58.7 ± 8.64% humidity). Significantly higher mean maximum power values were recorded in the second repetition under QSC conditions (1731,8 ± 214,4 W) (p = 0.025). A significantly longer time to reach maximum power was also recorded under TNC conditions compared to QSC conditions in repetition 2 (1,32 ± 0,33 s), (1,05 ± 0,29 s) (p = 0.016) and 6 (1,41 ± 0,48 s), (1,17 ± 0,25) (p = 0.036). There was a significantly higher rate of power loss, between repetition 2 (p = 0.023) and 4 (p = 0.043) under QSC conditions, compared to TNC. Considering the biochemical parameters, a significantly higher pO2 concentration was registered under QSC conditions in the 10th repetition (p = 0.006). The ambient temperature during exercise should be taken into account to determine the anaerobic exercise capacity of the athletes. At higher temperatures, there is a greater capacity for maximal effort, in terms of maximal power achieved, but with a greater decrease in performance.